Managing the regulatory process : design, concepts, issues, and the Latin America and Caribbean story - Guasch, J. Luis.; Spiller, Pablo T. (Washington, D.C. : World Bank, 1999)
The book provides an overview of regulations, the processes of regulation, cost and benefits and some fundamental lessons from the experience with government regulations
Includes bibliographical references: p. 309-319.
osc 27/06/2016
Loans
Keywords: Trade regulation; Industrial policy; Deregulation